ASPECTS OF RELIABILITY, EFFICIENCY AND ENERGY SAVING OF GAS PIPELINES AND GAS SUPPLY SYSTEM EQUIPMENT - Lena Shatakishvili,; Dimitri Namgaladze,; Tornike Kiziria,; Grigol Khelidze,; Ketevan BerikaSvili, (International Journal of Innovative Technologies in Social Science, 2024)
To ensure the safe operation of gas pipelines of the gas supply system it is necessary to solve the problems of timely detection and elimination of leaks, as well as to determine the volume of natural gas leaks. The most complicated case is the leakage from underground gas pipelines, as gas filtration into the ground, its spreading from the leakage place and accumulation in underground cavities are determined by many factors. Natural gas leaks, in addition to losses, may cause damage to buildings and structures, threat to human health and life due to burning or explosion of the gas-air mixture, financial and economic costs in case of gas shortages, and fines for consumers. Thus, the causes of failures are mainly corrosion wear and local defects of various origins on the walls of gas pipelines, which reduce the capacity of gas pipelines, as well as deteriorate the physical condition of the pipe metal - causing its fatigue under prolonged exposure to operational loads. The listed causes of failures, except for the last one, are well studied. The methods of local defects detection are developed, which will contribute to the improvement of the process of operation and repair and restoration technologies of gas pipelines. In contrast to the existing approaches, the approach presented in the article assumes improvement of the process of operation and repair and restoration technologies of gas distribution networks on the basis of local defects detection methods developed by the authors and improvement of their reliability taking into account the data on the actual technical condition and characteristics of each group of reliability indicators of elements of gas distribution networks.